AI in Consumer Protection: a Bibliometric Analysis: AI dalam Perlindungan Konsumen: Analisis Bibliometrik - Muhammad, Fadil; Bagus Edhita Praja, Chrisna; Maitsaa’ Jaudah, Tsuroyyaa (Fundamental: Jurnal Ilmiah Hukum, 2025)
This study explores global research trends on the role of artificial intelligence (AI) in consumer protection law through bibliometric analysis. The research data is taken from the Scopus database with the keywords "Artificial Intelligence" and "Consumer Protection," with a period of 2001-2024. Through BiblioShiny, this analysis identified 134 documents showing an annual growth of 15.22%. The results show that India is the country with the most publications, followed by the United States and Germany. This study also reveals the impact of AI on consumer protection, including issues of data privacy, algorithm manipulation, and influence on consumer behavior. Thematic analysis reveals that topics such as artificial intelligence technology and its impact on data privacy are the main focus of researchers. This study provides an analysis of the first research on AI and Consumer Protection that appeared in 2001 with a significant spike in publications that occurred in 2020 of 14 articles which further increased to 27 in 2023-2024. Of these articles, Tiago Sérgio Cabral is the most prolific author, focusing on data privacy and AI regulation with the journal "Lecture Notes in Computer Science" being the main source of publications with 34 articles. India is said to be the country with the highest number of publications on AI and Consumer Protection followed by other countries such as the United States and Germany where collaboration between countries and continents plays a significant role in developing this topic.